Computed tomography-based analysis of foramen magnum and occipital condyles in adult Nigerians: an anatomical study - Muhammad, Fatima; Ahmad, Umar; Tawfiq-Zyoud, Tawfiq Yousef; Jibril, Murtala Muhammad; Kwairanga, Suleiman Hamidu; Suppiah, Subapriya (Universidad de la Frontera, 2025)
SUMMARY: Precise identification of craniometric points is pivotal in forensic and anthropological research for reliable and accurate gender determination. The foramen magnum and occipital condyles' morphology offers valuable data for this purpose. The study aimed to determine variations in the morphology of the foramen magnum and occipital condyles among a population of 100 individuals, using advanced Computed Tomography (CT) scan technology. We assessed a prospective cohort of 100 individuals who underwent cranial CT scans. The study focused on the morphological variations of the foramen magnum and occipital condyles, recording shapes such as oval, round, egg, tetragon, pentagon, hexagon, and irregular for the foramen magnum, and kidney-type, oval, S-like, 8-like, ring-like, and triangular for the occipital condyles. Notably, males demonstrated higher measurement values for most parameters, with the exception of the width of the occipital condyle, where females presented larger dimensions. Furthermore, a strong positive correlation was observed between the measurements of the foramen magnum (length and width) and specific parameters of the occipital condyles. The study underscores the utility of foramen magnum dimensions, especially length, as a determinant in gender identification, with a success rate of 68 % in the studied population. This research enhances our understanding of cranial morphology and its applications in forensic and anthropological investigations.